Mortality Related Risk Factors in High-Risk Pulmonary Embolism in the ICU - Begüm Ergan; Recai Ergün; Taner Çalışkan; Kutlay Aydın; Murat Emre Tokur; Yusuf Savran; Uğur Koca; Bilgin Cömert; Necati Gökmen (Canadian Respiratory Journal)
Introduction. We sought to identify possible risk factors associated with mortality in patients with high-risk pulmonary embolism (PE) after intensive care unit (ICU) admission. Patients and Methods. PE patients, diagnosed with computer tomography pulmonary angiography, were included from two ICUs and were categorized into groups: group 1 high-risk patients and group 2 intermediate/low-risk patients. Results. Fifty-six patients were included. Of them, 41 (73.2%) were group 1 and 15 (26.7%) were group 2. When compared to group 2, need for vasopressor therapy (0 vs 68.3%; p<0.001) and need for invasive mechanical ventilation (6.7 vs 36.6%; p=0.043) were more frequent in group 1. The treatment of choice for group 1 was thrombolytic therapy in 29 (70.7%) and anticoagulation in 12 (29.3%) patients. ICU mortality for group 1 was 31.7% (n=13). In multivariate logistic regression analysis, APACHE II score >18 (OR 42.47 95% CI 1.50–1201.1), invasive mechanical ventilation (OR 30.10 95% CI 1.96–463.31), and thrombolytic therapy (OR 0.03 95% CI 0.01–0.98) were found as independent predictors of mortality. Conclusion. In high-risk PE, admission APACHE II score and need for invasive mechanical ventilation may predict death in ICU. Thrombolytic therapy seems to be beneficial in these patients.